CMBEAR: Python‐Based Recharge Estimator Using the Chloride Mass Balance Method in Australia. Issue 3 (28th December 2021) - Irvine, Dylan J.; Cartwright, Ian
Abstract: The chloride mass balance (CMB) method is widely used to estimate long‐term rates of groundwater recharge. In regions where surface water runoff is negligible, recharge can be estimated using measurements of chloride concentrations of groundwater and precipitation, and an estimate of long‐term average rainfall. This paper presents the Chloride Mass Balance Estimator of Australian Recharge (CMBEAR), a Jupyter (Python) Notebook that is set up to rapidly apply the CMB method using gridded maps of chloride deposition rates across the Australian continent. For an Australian context, the chloride deposition rate and rainfall maps have been provided. Thus, CMBEAR requires only a spreadsheet with the groundwater chloride concentration, the latitude and longitude of the sample location, and some simple user inputs. CMBEAR may be easily applied in other regions, providing that a gridded chloride deposition map is available. Recharge estimates from CMBEAR are compared against published applications of the CMB method. CMBEAR is also applied to a large dataset from the Northern Territory and is used to produce a gridded map of recharge for western Victoria. CMBEAR provides a reproducible and straightforward approach to apply the CMB method to estimate groundwater recharge. Abstract : Article impact statement : Python tool presented that provides an automated and reproducible approach to recharge estimation using the chloride mass balance method.